2019
DOI: 10.1096/fj.201901265r
|View full text |Cite
|
Sign up to set email alerts
|

The annexin A1/FPR2 signaling axis expands alveolar macrophages, limits viral replication, and attenuates pathogenesis in the murine influenza A virus infection model

Abstract: Pattern recognition receptors (PRRs) are key elements in the innate immune response. Formyl peptide receptor (FPR) 2 is a PRR that, in addition to proinflammatory, pathogen‐derived compounds, also recognizes the anti‐inflammatory endogenous ligand annexin A1 (AnxA1). Because the contribution of this signaling axis in viral infections is undefined, we investigated AnxA1‐mediated FPR2 activation on influenza A virus (IAV) infection in the murine model. AnxA1‐treated mice displayed significantly attenuated pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 91 publications
1
41
0
Order By: Relevance
“…6). This was particularly the case with FPR2, which has previously been noted in hypothalamic microglia (68), and which, in addition to binding viral peptides (see for example (60,69)), could play a role in neurodegenerative disorders, and mediate either pro-inflammatory or anti-inflammatory mechanisms (reviewed in (70)(71)(72)).…”
Section: Discussionmentioning
confidence: 85%
“…6). This was particularly the case with FPR2, which has previously been noted in hypothalamic microglia (68), and which, in addition to binding viral peptides (see for example (60,69)), could play a role in neurodegenerative disorders, and mediate either pro-inflammatory or anti-inflammatory mechanisms (reviewed in (70)(71)(72)).…”
Section: Discussionmentioning
confidence: 85%
“…Because overactivation of the innate immune response is often correlated with excessive and deleterious tissue damage, e.g., in influenza A virus (IAV) infection, targeting the FPR family might represent a novel approach to balance innate immunity. Indeed, our previous studies revealed the advantageous use of the host-derived anti-inflammatory N-terminal annexin A1 peptide Ac-2-26, a pan-FPR agonist [46] to counteract viral load and mortality in a preclinical murine IAV infection model [47], thus encouraging the development of novel FPR-based therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, the significant therapeutic potential of AnxA1:FPR2 was recently uncovered during a murine model of viral pneumonia. The proresolving actions of AnxA1 were shown to enhance host response during Influenza infection through the expansion of alveolar macrophages which protected mice from pathology . Collectively, our results provide evidence for the protective role of AnxA1 during respiratory infections.…”
Section: Discussionmentioning
confidence: 99%